The misfits [videorecording (DVD)] - Roth, Tim; Brosnan, Pierce; Chung, Jamie, 1983-; Corfield, Hermione, 1993-; Cannon, Nick, 1980- (Paramount Home Entertainment, 2020)
A band of modern-day Robin Hoods recruits a renowned thief to help steal millions in gold bars stashed underneath one of the world's most secure prisons.